Hak Waris Anak Perempuan Menurut Hukum Adat Batak - Axel Gultom; Johan Binsar Rockefeller Manurung; Muhammad Zadith Taqwa; Dwi Desi Yayi Tarina (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This study examines the inheritance rights of daughters under Batak Toba customary law, which is based on a patrilineal kinship system. The background of the problem highlights the prioritization of inheritance distribution to sons as the successors of the clan (marga), resulting in daughters traditionally not receiving inheritance, as they are considered to join their husband’s clan after marriage. The research problems include the regulation of inheritance rights, the legal standing of Supreme Court Decision Number 179 K/Sip/1961, and its current implementation in society. The research method is normative juridical, employing a literature study approach and qualitative analysis of positive legal norms. The results indicate that the decision recognizes the inheritance rights of daughters, although it does not entirely eliminate customary practices. Its implementation varies: traditional communities tend to maintain the old norms, while urban societies are more inclusive through family deliberation. It is concluded that Batak Toba customary law is undergoing dynamic adaptation toward national principles of justice, emphasizing the harmonization between customary law and modern legal systems.